2021
DOI: 10.1093/ofid/ofab050
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Cohort of Fluvoxamine for Early Treatment of Coronavirus Disease 19

Abstract: We report a real-world experience using fluvoxamine for coronavirus disease 19 (COVID-19) in a prospective cohort in the setting of a mass outbreak. Overall, 65 persons opted to receive fluvoxamine 50mg twice daily and 48 declined. Incidence of hospitalization was 0% (0/65) with fluvoxamine and 12.5% (6/48) with observation alone. At 14 days, residual symptoms persisted in 0% (0/65) with fluvoxamine and 60% (29/48) with observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
164
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(172 citation statements)
references
References 3 publications
6
164
1
1
Order By: Relevance
“…Fifteen FIASMAs [ 20 , 25 , 29 , 30 , 31 , 32 , 46 , 53 , 54 , 73 , 75 , 76 , 77 , 78 , 82 , 88 , 101 , 102 , 103 ] have been studied using epidemiological-clinical studies or case reports (amiodarone, amitriptyline, amlodipine, carvedilol, chlorpromazine, clomipramine, desloratadine, fluoxetine, fluvoxamine, hydroxyzine, loperamide, loratadine, melatonine, paroxetine, and sertraline). Among the 15 FIASMAs, only amlodipine [ 32 ] and fluvoxamine [ 75 ] were studied using randomized double-blind clinical studies (see Table 2 ).…”
Section: Update (16 June 2021) On Studies With Fiasmas In the Sars-cov-2 Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen FIASMAs [ 20 , 25 , 29 , 30 , 31 , 32 , 46 , 53 , 54 , 73 , 75 , 76 , 77 , 78 , 82 , 88 , 101 , 102 , 103 ] have been studied using epidemiological-clinical studies or case reports (amiodarone, amitriptyline, amlodipine, carvedilol, chlorpromazine, clomipramine, desloratadine, fluoxetine, fluvoxamine, hydroxyzine, loperamide, loratadine, melatonine, paroxetine, and sertraline). Among the 15 FIASMAs, only amlodipine [ 32 ] and fluvoxamine [ 75 ] were studied using randomized double-blind clinical studies (see Table 2 ).…”
Section: Update (16 June 2021) On Studies With Fiasmas In the Sars-cov-2 Infectionmentioning
confidence: 99%
“…Among the 19 human studies, there were two case reports on amiodarone [ 20 ] or loratadine [ 88 ], four retrospective studies that have explored the association between one FIASMAs (carvedilol [ 25 , 53 ], hydroxyzine [ 77 , 101 ], loratadine [ 77 ], melatonine [ 25 , 53 ], paroxetine [ 53 ]) and the negativity or positivity on a PCR test, four prospective studies on fluvoxamine [ 75 , 76 ], melatonine [ 102 ] or amlodipine [ 32 ] including two randomized clinical trial [ 32 , 75 ], 4 retrospective studies on mortality in hospitalized COVID-19 patients on amlodipine [ 29 , 30 , 31 ] or melatonine [ 82 ], one observational study on low rate of COVID-19 infection in psychiatric patients treated by antipsychotics comparatively to nurses or physicians [ 73 ], 4 retrospective studies on mortality or intubation on hospitalized COVID-19 patients on amiodarone, amitriptyline, amlodipine, chlorpromazine, clomipramine, desloratadine, fluoxetine, hydroxyzine, paroxetine and sertraline [ 46 , 54 , 78 , 103 ].…”
Section: Update (16 June 2021) On Studies With Fiasmas In the Sars-cov-2 Infectionmentioning
confidence: 99%
“…Another study showed that with the use of Fluvoxamine for early treatment of COVID-19, the incidence of hospitalization was 0% with Fluvoxamine and 12.5% with observation alone. At 14 days, 0% of Fluvoxamine-treated people had persistent residual symptoms compared to 60% among people who opted for no therapy [243].…”
Section: Antipsychotic and Antihistamine Compoundsmentioning
confidence: 96%
“…Of the completed studies, one randomized, double-blind clinical trial with 152 subjects reported that fluvoxamine decreased clinical progression, defined as hypoxia coupled with either shortness of breath or hospitalization, from 8% with observation alone to 0% with fluvoxamine at up to 300 mg daily [ 87 ]. In a second study with 65 patients taking fluvoxamine and 48 patients without, the incidence of hospitalization was 0% and 12.5%, respectively, and at 14 days, the persistence of residual symptoms was at 0% and 60% for fluvoxamine and no treatment, respectively [ 88 ]. While both these studies are small, and the second does not include any placebo (only untreated patients), they both show very promising initial data suggesting that fluvoxamine can prevent the required hospitalization, intubation, and death.…”
Section: Sigma Receptor Drugs and Sars-cov-2mentioning
confidence: 99%